Sustained intracellular calcium rise mediates neuronal mitophagy in models of autosomal dominant optic atrophy - Zaninello, M.; Palikaras, K.; Sotiriou, A.; Tavernarakis, N.; Scorrano, L. (Cell Death Differ, 2021)
Mitochondrial dysfunction and mitophagy are often hallmarks of neurodegenerative diseases such as autosomal dominant optic atrophy (ADOA) caused by mutations in the key mitochondrial dynamics protein optic atrophy 1 (Opa1). However, the second messengers linking mitochondrial dysfunction to initiation of mitophagy remain poorly characterized. Here, we show in mammalian and nematode neurons that Opa1 mutations trigger Ca(2+)-dependent mitophagy. Deletion or expression of mutated Opa1 in mouse retinal ganglion cells and Caenorhabditis elegans motor neurons lead to mitochondrial dysfunction, increased cytosolic Ca(2+) levels, and decreased axonal mitochondrial density. Chelation of Ca(2+) restores mitochondrial density in neuronal processes, neuronal function, and viability. Mechanistically, sustained Ca(2+) levels activate calcineurin and AMPK, placed in the same genetic pathway regulating axonal mitochondrial density. Our data reveal that mitophagy in ADOA depends on Ca(2+)-calcineurin-AMPK signaling cascade.
Zaninello, MartaPalikaras, KonstantinosSotiriou, AggelikiTavernarakis, NektariosScorrano, LucaengGA695190/EC | EC Seventh Framework Programm | FP7 Ideas: European Research Council (FP7-IDEAS-ERC - Specific Programme: "Ideas" Implementing the Seventh Framework Programme of the European Community for Research, Technological Development and Demonstration Activities (2007 to 2013))GA737599/EC | EU Framework Programme for Research and Innovation H2020 | H2020 Priority Excellent Science | H2020 European Research Council (H2020 Excellent Science - European Research Council)GGP15091/Fondazione Telethon (Telethon Foundation)GGP19089/Fondazione Telethon (Telethon Foundation)EnglandCell Death Differ. 2021 Aug 13. pii: 10.1038/s41418-021-00847-3. doi: 10.1038/s41418-021-00847-3.